RNA splicing specificity determined by the coordinated action of RNA recognition motifs in SR proteins - Chandler, Sharon D. (The National Academy of Sciences of the USA, 1997)
Pre-mRNA splicing requires a large number of RNA-binding proteins that have one or more RNA-recognition motifs (RRMs). Among these is the SR protein family, whose members are essential for splicing and are able to commit pre-mRNAs to the splicing pathway with overlapping but distinct substrate specificity. Some SR proteins, such as SC35, contain an N-terminal RRM and a C-terminal arginine/serine-rich (RS) domain, whereas others, such as SF2/ASF, also contain a second, atypical RRM. Although both the RRMs and the RS domain of SR proteins are required for constitutive splicing, it is unclear which domain(s) defines their substrate specificity, and whether two RRMs in a given SR protein function independently or act coordinately. Using domain swaps between SC35 and SF2/ASF and a functional commitment assay, we demonstrate that individual domains are functional modules, RS domains are interchangeable, and substrate specificity is defined by the RRMs. The atypical RRM of SF2/ASF does not appear to function alone in splicing, but can either activate or suppress the splicing specificity of an N-terminal RRM. Therefore, multiple RRMs in SR proteins act coordinately to achieve a unique spectrum of pre-mRNA substrate specificity.